Graphite intercalation compounds - Fischer, John E.; Thompson, Thomas E. (Physics today, 1978)
Solid-state physicists are turning more and more to complex synthetic materials in their search for novel phenomena and potentially useful properties. Many of these materials are highly anisotropic, so that interatomic interactions can for all practical purposes be neglected along one or two crystal axes. One of the oldest classes of prototype systems for exploring phenomena predicted to occur in two-dimensional systems are graphite intercalation compounds. These consist of stacks of one or more layers of hexagonally arrayed carbon atoms, alternating with monolayers of guest atoms or molecules. Striking changes in the properties of both host and guest result from intercalation. In addition to their quasi-two-dimensional behavior, fundamental interest centers on their variable anisotropy, which results from the fact that the strength of the interlayer interactions depends on the nature of the intercalated species.